Arquitectura del sonido: inaugural musika viva in bogotá. 1969 (2012)
Arquitectura del Sonido was the inaugural event of MusikaViva, a multidisciplinary creation group from Bogotá inspiredby the tenets of John Cage. The group led by GustavoSorzano, experimented with the possibilities of architecturalspace in creative events with public participation.This article seeks to contribute to the understanding of thebeginnings of conceptual art in Colombia and explores twomain conceptual lines: the construction of space throughthe experience and the desire for total artwork.